Circulating biomarkers for abdominal aortic aneurysm: what did we learn in the last decade? - Moris, D N; Georgopoulos, S E (International angiology, 2013)
Abdominal aorta aneurysm (AAA) is a serious threat for human life, especially in such cases when it is asymptomatic until aneurysm rupture, which is a general cause of death in AAA subjects. We aim to give a conceptual description of the potential biomarkers that can correlate and predict the natural history of an AAA. The MEDLINE/PubMed database was searched for publications with the medical subject heading "abdominal aortic aneurysms (AAA)" and the keyword "biomarkers". We restricted our search to English till January 2012. We focused on human studies that reported aneurysm size, expansion rates and/or rupture and the studied biomarkers. In this review we included 94 articles (4 reviews) that were accessible and available in English. We excluded articles referred exclusively to thoracic aneurysms and cardiac studies. There are no specific laboratory markers that would allow one to distinguish in a simple way between aneurysm bearers and the healthy population. Serum elastase peptides seem still to be sufficient biomarkers to predict expansion and rupture, but advanced techniques (ELISA) and larger studies are needed to establish its exact role. Plasmin-antiplasmin complexes (PAP) may also have clinical potential. Newer biomarkers may also have a role, not well established yet. Beyond that, there are many limitations related to the fact that many biomarkers related with AAA outcome are not disease specific, due to their established correlation with atherosclerosis. Future research is required to establish the underlying relations between these biomarkers and their role in AAA pathophysiology.